The Effect of First Aid Education on the Level of Knowledge Regarding Syncope Management in the KSR PMI Unit of Universitas Muhammadiyah Purwokerto - Erika Anggraeni; Endiyono Endiyono (UM Purwokerto Press, 2024)
Background: Syncope is an emergency condition characterized by sudden loss of consciousness due to inadequate blood flow to the brain, lack of oxygen and symptoms of other chronic diseases. The global incidence of syncope is estimated at 12 million cases per year. Syncope incidents on campus require help quickly and appropriately. The KSR PMI Unit of Muhammadiyah University Purwokerto is a volunteer corps organization that provides first aid for syncope. Objective: To determine the effect of first aid education on syncope management on the level of knowledge of members of the PMI KSR Unit, Purwokerto Muhammadiyah University. Method: This research uses quantitative research methods with a pre-experimental design with a one-group pre-test-post-test approach. The sample consisted of 35 respondents selected through total sampling technique. Results: The research results obtained a P value of 0.01, with an average knowledge score before being given the intervention of 8.46, with a minimum score range of 6 to a maximum score of 11. After receiving the intervention the average knowledge score increased to 14.29, with a minimum score of 11 and a maximum score of 15. Conclusion: There is an influence of first aid education on syncope management on the level of knowledge of members of the PMI KSR Unit, Purwokerto Muhammadiyah University.